WE3.2: GenderUp: A conversational method for responsible Scaling - Rietveld, Anne M.; Teeken, Béla (Bioversity International and the International Center for Tropical Agriculture, 2022)
GenderUp is a conversational method for designing responsible scaling strategies in a particular context. It is intended to be used by project teams who want to scale the use of an agricultural innovation in a socially inclusive way and who want to prevent undesirable outcomes. GenderUp supports users to identify gender and other relevant diversity among innovation users and to improve the scaling strategy by optimizing the inclusion of relevant social groups and by anticipating unintended negative consequences for different social groups. GenderUp is a web-based tool that takes project teams on a journey through the stages of developing or improving a scaling strategy. The journey is facilitated by someone with a background in gender studies who is familiar with the tool. The objective of this capacity building session is to familiarize CGIAR gender researchers with GenderUp. Participants will learn about the objectives and functioning of the tool. The session is relevant to gender researchers who want to use GenderUp with project teams to embark on a socially inclusive scaling journey. The session will enable them to discover the potential of GenderUp. Participants might become full-fledged GenderUp facilitators themselves. This session is a first step in that direction*. GenderUp is a conversational method, designed to evoke discussion on relevant social issues that pertain to scaling. The session will discuss and lead participants through the web-based tool. * To facilitate a GenderUp journey independently we envisage prospective facilitators, apart from this session, to join in on a real application journey and listen in and learn from the facilitator.